Validity and Reliability of the Semmes-Weinstein Monofilament Test and the Thumb Localizing Test in Patients With Stroke - Suda, Mabu; Kawakami, Michiyuki; Okuyama, Kohei; Ishii, Ryota; Oshima, Osamu; Hijikata, Nanako; Nakamura, Takuya; Oka, Asako; Kondo, Kunitsugu; Liu, Meigen (Frontiers in Neurology, 2021)
Background: Somatosensory impairment is common in patients who have had a stroke and can affect their motor function and activities of daily living (ADL). Various examinations have been developed. However, the reliability and validity of few of them have been verified. Objective: The purpose of this study was to verify the reliability and validity of two convenient clinical examinations, the Semmes-Weinstein Monofilament Test (SWMT) and the Thumb Localizing Test (TLT) as indices of somatosensory impairment of the upper extremity (UE) in patients with chronic post-stroke hemiparesis. Methods: Fifty patients with chronic stroke (median time after onset of stroke, 848 days, mean age 57 [standard deviation 14] years) were enrolled. Examiners learned the original method of the SWMT and the TLT rigorously. The TLT procedure was partially modified by dividing the location of the patient’s thumb into four spaces. Two examiners evaluated the SWMT and the TLT for two days, and intra-rater and inter-rater reliabilities were calculated using weighted kappa statistics. In addition to this, the evaluator size score of the SWMT was assessed with Bland-Altman analysis to evaluate systematic bias. The Stroke Impairment Assessment Set (SIAS) sensory items were used to assess validity, and Spearman’s rank correlation coefficients were calculated. Results: Intra/inter-rater agreements of the SWMT grade score were 0.89 (thumb, 95%CI: 0.83-0.95)/ 0.75 (0.60-0.91) and 0.80 (index finger, 0.67-0.93)/0.79 (0.66-0.92), and of the TLT they were 0.83 (navel level proximal space, 0.71-0.95)/ 0.83 (0.73-0.92), 0.90 (navel level distal space, 0.85-0.96)/ 0.80 (0.69-0.90), 0.80 (shoulder level proximal space, 0.68-0.92)/ 0.77 (0.65-0.89), and 0.87 (shoulder level distal space, 0.80-0.93)/ 0.80 (0.68-0.92) (P<.001, each item). The MDC of the SWMT evaluator size was 1.28 to 1.79 in the inter-rater test and 1.94 to 2.06 in the intra-rater test. The SWMT grade score showed a strong correlation with the SIAS light touch sensation item (r=0.65, p<.001), as did the TLT with the SIAS position sense item (r= -0.70 - -0.62, p<.001 each space). Conclusions: These tests can be used as reliable sensory examinations of the UE in patients with chronic stroke, and especially for the SWMT, it is more reliable for screening.